Forthcoming Networks and Sustainability in the AIoT Era Second International Conference FoNeS-AIoT 2024 - Volume 1 - Rasheed, Jawad; Abu-Mahfouz, Adnan M.; Fahim, Muhammad (Lecture Notes in Networks and Systems,, 2024)
VIII, 458 p. 236 illus., 202 illus. in color.